2021
DOI: 10.1002/epi4.12449
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among caregivers of children with epilepsy: A cross‐sectional study at Eastern Nepal

Abstract: Objective To assess the quality of life among caregivers of children with epilepsy in a tertiary care center of eastern Nepal. Methods A cross‐sectional study was conducted among primary caregivers of children with epilepsy, who accompanied their child in child neurology clinic. Consecutive sampling was done, and 106 respondents were interviewed. Data were collected using World Health Organization Quality of Life‐BREF (WHOQOL‐BREF) scale and analyzed using Statistical Package for the Social Sciences. Descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
3
4
0
1
Order By: Relevance
“…A recent study showed that mothers of persons diagnosed with autistic spectrum disorder represent the main caregivers, who report a relatively high burden particularly associated with a care towards children aged 6 and 12 years, increasing in correlation with the severity of autism. Considering reports of married women taking care of their child with special needs, the results of this study coincide with those found by other authors [21,24], who revealed that the wellbeing of married female caregivers may be maintained, as their ability to share tasks with their husbands can also positively affect their perception of QoL [23]. These interesting findings were also observed in our study, despite the fact that the family income was in the range of two to five minimum wages, allocating families to a group of low socioeconomic status and compromising their livelihood.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A recent study showed that mothers of persons diagnosed with autistic spectrum disorder represent the main caregivers, who report a relatively high burden particularly associated with a care towards children aged 6 and 12 years, increasing in correlation with the severity of autism. Considering reports of married women taking care of their child with special needs, the results of this study coincide with those found by other authors [21,24], who revealed that the wellbeing of married female caregivers may be maintained, as their ability to share tasks with their husbands can also positively affect their perception of QoL [23]. These interesting findings were also observed in our study, despite the fact that the family income was in the range of two to five minimum wages, allocating families to a group of low socioeconomic status and compromising their livelihood.…”
Section: Discussionsupporting
confidence: 91%
“…Schreiner et al [28] observed that a ZBI cut-off score ranging from 24 to 26 has significant predictive validity for identifying caregivers susceptible to depression. The authors stated that these caregivers could be reliably identified by administering the ZBI scale alone and their data confirm the anxiety-related overload shown in other studies [21,23]. The moderate overload found seems consistent with the findings of several other studies [26][27][28], although Moreira et al [29] and Estrada-Hernandez [23] demonstrated more intense overload.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…[ 5 ] Various aspects of family life can be altered and affected indirectly due to epilepsy as it has been associated with loss of control, independence, fear, confusion, discrimination, problems related to the side effects of antiepileptic drugs, depression, and stigmatization. [ 1 6 7 ] Studies show that having a child with epilepsy produces an elevated stress level on the caregiver that is greater than that noted with other chronic conditions. [ 8 ] They are subjected to long-term stressors, which affect their daily lives and health such as disrupted sleep patterns and sleep deprivation, high rates of depression for both mothers and fathers of children with epilepsy increasing the risk for the poor quality of life (QOL).…”
Section: Introductionmentioning
confidence: 99%